Dengue-Associated Posterior Reversible Encephalopathy Syndrome Occurring in a Woman with 32 Weeks Pregnancy: A Case Report from Bangladesh - Ahmed, Mohiuddin (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Posterior reversible encephalopathy syndrome (PRES) is an increasingly well recognised reversible clinicoradiological condition. Dengue can cause various neurologic complications like encephalitis, myelitis, Guillain-Barré syndrome (GBS), and myositis, which are increasingly being recognized in addition to the more common manifestations of plasma leakage and coagulopathy. Posterior reversible encephalopathy syndrome (PRES) is rare in dengue, although the pathophysiology of endothelial dysfunction likely underlies both. Here we report a case of dengue-associated posterior reversible encephalopathy syndrome in a pregnant woman J Bangladesh Coll Phys Surg 2023; 41: 99-100